2014
DOI: 10.3892/or.2014.3270
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evidence of the relationship between aspirin and breast cancer risk (Review)

Abstract: Abstract. In the search for new therapeutic alternatives against cancer, either as a preventive treatment or for advanced stages, it is common to appeal to well-known drugs used for the treatment of other diseases that may interfere with the metabolic pathways involved in carcinogenesis. Non-steroidal anti-inflammatory drugs (NSAIDs) display anticancer activity through the inhibition of the COX-2 enzyme, triggering processes such as apoptosis, a reduction in proliferation and inhibition of carcinogenesis. Brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 62 publications
(77 reference statements)
1
7
0
1
Order By: Relevance
“…Moreover, a recent clinical analysis reported that regular aspirin use was associated with a lower risk of cancer-specific mortality in individuals already diagnosed with colorectal cancer [ 183 ]. Similar observations have been reported for the chemopreventive role of aspirin in breast cancer [ 184 , 185 ]. Together, these results suggested that the chemopreventive benefits of aspirin might only manifest after long-term continuous administration.…”
Section: Therapeutic Insights From Mouse Modelssupporting
confidence: 89%
“…Moreover, a recent clinical analysis reported that regular aspirin use was associated with a lower risk of cancer-specific mortality in individuals already diagnosed with colorectal cancer [ 183 ]. Similar observations have been reported for the chemopreventive role of aspirin in breast cancer [ 184 , 185 ]. Together, these results suggested that the chemopreventive benefits of aspirin might only manifest after long-term continuous administration.…”
Section: Therapeutic Insights From Mouse Modelssupporting
confidence: 89%
“…However, these results must be interpreted carefully, as exposure categories have been defined heterogeneously among the studies which have weakened the validity of the pooled estimates. In addition, Mangiapane S [5] and Jacobo-Herrera NJ [22] have pointed out that the relationship between breast cancer and aspirin, dosage, time and frequency of aspirin use have yet to be established. Therefore, it is necessary to perform this dose-response meta-analysis with cohort design to offer a more confident and exhaustive solution to a possible inverse association between breast cancer risk and aspirin intake [22].…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin synthesis through arachidonic acid and the possible effects of cyclooxygenase inhibitors as chemopreventive agents of breast cancer by the intracellular accumulation of arachidonic acid, which directly promotes apoptosis and attenuation of positive feedback for proliferation and survival. COX, cyclooxygenase; COXIBs, COX2 selective inhibitors; PG, prostaglandin; TXA 2 , thromboxane A 2 ( Jacobo-Herrera et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%